Strong phenological differences between two populations of a Neotropical funnel-web wolf spider - González Pérez, María de la Macarena (2014)
Comparisons of phenological patterns among populations within a species are uncommon in arachnids. Aglaoctenus lagotis is a wolf spider that lives in funnel-webs across South America. The aim of this study was to describe the phenological patterns of two distant populations of A. lagotis (central Argentina, CA, and southern Uruguay, SU). Individuals of each population were sighted along transects, every month for two years. The CA and SU populations differed in their phenological patterns (Wald χ2 = 966.94, df = 66; p <0.001). The CA population showed a spring–summer unified reproductive season and immature individuals overwintered. SU showed the sexual period during autumn, the maternal period during spring–summer and the females, mostly mated, overwintered. These strong differences imply temporal isolation in mating possibilities between both populations. The differences encountered could be due to phenotypic plasticity or have a phylogenetic basis. Interpopulation studies of other features of A. lagotis would show whether they also vary, suggesting speciation.